INFLUENCE OF ACADEMIC ACHIEVEMENT, MOTIVATION AND SELF REGULATED LEARNING ON THE CRITICAL THINKING IN THE UNDERGRADUATE MEDICAL STUDENTS - Muhammad Alif Farhan (2023)
Objective: This study aims to examine the relationship between academic achievement, motivation, self-regulated learning, and critical thinking ability among medical students. Methods: An analytical research design with a cross-sectional approach was employed for this study. The research was conducted at UPN "Veteran" Jakarta from November 2022 to January 2023. The sample comprised 145 medical students. The Critical Thinking Tools (CriTT) questionnaire was used to measure critical thinking skills, while academic achievement was assessed using Grade Point Average (GPA). Motivation and self-regulated learning were evaluated using The Motivated Strategies for Learning Questionnaire (MSLQ). Data analysis was conducted using the Spearman rank test and Multiple linear regression in SPSS version 24. Results: Univariate analysis revealed that the respondents demonstrated an average critical thinking score of 198.13 ± 25.14. The average GPA of the respondents was 3.60 ± 0.16. The respondents exhibited an average motivation score of 73.69 ± 8.27 and an average self-regulated learning score of 184.12 ± 19.68. Bivariate analysis showed significant relationships between critical thinking ability and motivation (p=0.000) as well as self-regulated learning (p=0.000). However, there was no significant relationship between critical thinking ability and academic achievement (p=0.465). Furthermore, this study found a significant relationship between academic achievement, motivation, and self-regulated learning when predicting critical thinking skills simultaneously. Conclusion: This study reveals significant associations between critical thinking ability and motivation, as well as self-regulated learning among medical students. However, no significant relationship was found between critical thinking ability and academic achievement. The findings highlight the importance of motivation and self-regulated learning in fostering critical thinking skills. Further research is needed to explore additional factors that may contribute to the development of critical thinking abilities in medical education. Keywords: academic achievement, critical thinking, motivation, self-regulated learning.